piRNA-823 Is Involved in Cancer Stem Cell Regulation Through Altering DNA Methylation in Association With Luminal Breast Cancer - Ding, Xin; Li, Ya; Lü, Jinhui; Zhao, Qian; Guo, Yuefan; Lu, Ziye; Ma, Wenjing; Liu, Pengfei; Pestell, Richard G.; Liang, Chunli; Yu, Zuoren (Frontiers in Cell and Developmental Biology, 2021)
Cancer stem cells (CSCs) are believed to be the main source of cancer relapse and metastasis. PIWI-interacting small non-coding RNAs (piRNAs) have been recently recognized to be relevant to cancer biology. Whether and how piRNAs regulate human cancer stem cells remain unknown. Herein, upregulation of piR-823 was identified in the tested luminal breast cancer cells, especially in luminal subtype of breast CSCs. Enforced expression or targeted knockdown of piR-823 demonstrated its oncogenic function in regulating cell proliferation and colony formation in MCF-7 and T-47D breast cancer cells. In addition, piR-823 induced ALDH (+) breast CSC subpopulation, promoted the expression of stem cell markers including OCT4, SOX2, KLF4, NANOG, and hTERT, and increased mammosphere formation. Tail-vein injection of magnetic nanoparticles carrying anti-piR-823 into the mammary gland tumor-burden mice significantly inhibited tumor growth in vivo. DNA methyltransferases (DNMTs) including DNMT1, DNMT3A and DNMT3B were demonstrated to be the downstream genes of piR-823, which regulate gene expression by maintaining DNA methylation. piR-823 increased the expression of DNMTs, promoted DNA methylation of gene Adenomatous Polyposis Coli (APC), thereby activating Wnt signaling and inducing cancer cell stemness in luminal subtype of breast cancer cells. The current study not only revealed a novel mechanism through which piRNAs contribute to tumorigenesis in breast cancer by regulating CSCs, but also provided a therapeutic strategy using non-coding genome in suppression of human breast cancer.